Design and analysis of a photovoltaic‐powered charging station for plug‐in hybrid electric vehicles in college campus. Issue 4 (24th November 2022) - Sureshbabu,; Padmanabhan, Suresh; Subramanian, Ganesan; Stonier, Albert Alexander; Peter, Geno; Ganji, Vivekananda
Abstract: Photovoltaic‐powered electric transportation systems are gaining global momentum owing to their superior enactment and zero carbon emissions. With a growing number of electric vehicles (EVs) on the road, implementation of efficient and well‐organised charging stations is extremely indispensable. The authors investigate the feasibility of creating a charging station for plug‐in‐hybrid EVs at an educational institution, E.G.S. Pillay Engineering College, Nagapattinam, Tamil Nadu, India (10°48.2′N, 79°50.1′E). The statistics related to the solar radiations of the Nagapattinam region are employed to find out the energy availability for the EV charging station (EVCS) and the requirement for grid connection. The authors use a hybrid optimisation model for an electric renewable (HOMER) simulator to determine the optimum specification of the proposed EVCS. Also, the authors carry out a techno‐economic study against the specified load requirement to evaluate the potential of the charging station. The solar irradiance data obtained from NASA ground climatology and the solar power dataset of the designated site are used to realise the precise fallouts. The optimisation results provide minimum annual system cost and reliable power to the EVs. Based on these results, an EVCS is erected in the college campus to charge plug‐in hybrid electric vehicles. The established EVCS contains 3 kW EV charger operating as a microgrid and includes nine solar panels with 335 W each, 48 V, 150 Ah specification. The authors use solar photovoltaic (PV) panels using Copper Indium Selenide‐Zinc sulfide (CISZS) quantum dots for maximising energy yield from the EVCS. The authors consider that eight different charging profiles for different months are employed for estimating the solar irradiance probability density in the designated site. From this study, the authors can conclude that Gaussian mixer model (G4) profile is optimum for the Nagapattinam region to install a potential and reliable EVCS. Abstract : Photovoltaic‐powered electric transportation systems are gaining global momentum owing to their superior enactment and zero carbon emissions. With a growing number of electric vehicles (EVs) on the road, implementation of efficient and well‐organised charging stations is extremely indispensable. In this work, we investigate the feasibility of creating a charging station for plug‐in‐hybrid EVs at an educational institution, E.G.S. Pillay Engineering College, Nagapattinam, Tamil Nadu, India (10°48.2′N, 79°50.1′E). The statistics related to the solar radiations of the Nagapattinam region are employed in this work to find out the energy availability for the EV charging station (EVCS) and the requirement for grid connection. We use a hybrid optimisation model for an electric renewable (HOMER) simulator to determine the optimum specification of proposed EVCS. Also, we carry out a techno‐economic study against the specified load requirement to evaluate the potential of the charging station. The solar irradiance data obtained from NASA ground climatology and solar power dataset of the designated site are used to realise precise fallouts. The optimisation results provide minimum annual system cost and reliable power to the EVs. Based on these results, an EVCS is erected in the college campus to charge plug‐in hybrid electric vehicles. The established EVCS contains 3 kW EV charger operating as a microgrid and includes nine solar panels with 335 W each, 48 V, and 150 Ah specification. In this work, we use solar photovoltaic (PV) panels using Copper Indium Selenide‐Zinc sulfide (CISZS) quantum dots for maximiszing energy yield from the EVCS. We consider eight different charging profiles for different months, which are employed for estimating solar irradiance probability density in the designated site. From this study, we can conclude that Gaussian mixer model (G4) profile is optimum for the Nagapattinam region to install a potential and reliable EVS.